Influence of a Fluoridated Medium with Different pHs on Commercially Pure Titanium-Based Implants - Sartori, Rafael [UNESP]; Correa, Cassia Bellotto [UNESP]; Marcantonio, Elcio [UNESP]; Vaz, Luis Geraldo [UNESP] (Wiley-Blackwell, 2009)
Purpose: The objective of this study was to assess the influence of a fluoride medium with different pHs on the corrosion resistance of three commercially pure titanium-based dental implant commercial brands, under scanning electron microscopy (SEM) and EDS.Materials and Methods: Forty-two dental implants, from three commercial brands, were used. Five years of regular use of mouth rinsing, with NaF 1500 ppm content and two different pHs, were simulated by immersing the specimens into that medium for 184 hours.Results: SEM and EDS analyses demonstrated no evidence of corrosion on the specimens' surfaces after being submitted to fluoride ions or incorporation of fluoride ions to the set surface.Conclusion: It was possible to conclude that both the fluoride concentration and the pH of the solutions did not exert any influence upon implant corrosion resistance.
Keywords: Corrosion; fluoride; dental implants; titanium